Factor Analysis of Soil Nutrient Distribution Pattern under Different Plantations - Jha, M. N.; Gupta, M. K.; Pandey, Rajiv (Indian Forester, 2000)
Factor analysis of soil nutrient distribution pattern under Chir, Teak, Eucalyptus, Shish am and Khair, in Mussoorie Forest Division (U.P.) was studied. It was done to identify underlying factors that are responsible for correlation among nutrients under five plantations. Eigen values for the first four factors were > 0.90 and combined accounted for 77 percent of total variation in the soil supporting the five plantations. The four factor model explained > 90 percent of the variance in total phosphorus; 85 percent of the variance in organic matter and available nitrogen; and > 70 percent of the variance in total nitrogen, total potassium, and total sodium, available potassium and available phosphorus. However the four factor model explained only 62 percent of the variance in available potassium and 66 percent of the variance in total calcium. The four extracted factors are aggrading factor (36.6 percent), Sodium factor (16.16 percent), Phosphorus factor (12.67 percent) and total phosphorus factor (11.92 percent) obtain through varimax orthogonal factor analysis.